Anticyclonic Eddy Driving Significant Changes in Prokaryotic and Eukaryotic Communities in the South China Sea - Sun, Fulin; Xia, Xiaomin; Simon, Meinhard; Wang, Youshao; Zhao, Hui; Sun, Cuici; Cheng, Hao; Wang, Yutu; Hu, Shuibo; Fei, Jiao; Wu, Meilin (Frontiers in Marine Science, 2022)
Mesoscale eddies play an important role in ocean energy and material transport. However, the effect of eddies on bacterial and eukaryotic community and their ecological effects remains unclear, regarding anticyclonic eddies (ACE). In this study, bacterial and eukaryotic community composition was examined across an ACE in the South China Sea, using high-throughput sequencing of the 16S rRNA and 18S rRNA gene. Environmental variables reflected the hydrological characteristics of the ACE, which enhanced bacterial diversity and enhanced eukaryotic diversity in most water layers, relative to adjacent regions. Principal component analysis (PCoA) showed that bacterial and eukaryotic communities had significantly different compositions between inside and outside the eddy. An obvious effect of the ACE was the increase in abundance and depth distribution of small photosynthetic and heterotrophic bacteria, such as SAR11, Prochlorococcus, Rhodospirillales and Oceanospirillales. While ACE decreased the relative abundance of nutrient-rich phytoplankton (Bacillariophyta and Mamiellophyceae), resulted in more growth space for other eukaryotes that prefer oligotrophic environment (especially Fungi, Dictyochophyceae and Synurophyceae). Canonical correlation analysis (CCA) showed temperature, salinity, nitrate, phosphate and nitrite had significantly affected on microbial community. The special environment of ACE (especially temperature) shaped the composition of its specific microbe. This study shed important light on the effect of ACEs on environmental conditions to impact marine ecosystem structure.